Measurement of the time-dependent CP asymmetry in the B-0 ->phi K-0 decay - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
A measurement of the time-dependent CP asymmetry for the neutral B-meson decay B0 → φK0 was discussed. The study was carried by using a sample of B-meson pairs taken at the γ(4S) resonance with the BABAR detector at the PEP-II B-meson factory at SLAC. The CP eigenstates were reconstructed φK0s and φK 0L, where φ K+K-,K 0s → π+ π-, and K 0L was observed. The results show that the values of the CP-violations parameters were SφK = 0.47 ± 0.37(stat) +0.08-0.06.